Microplastics Differ Between Indoor and Outdoor Air Masses: Insights from Multiple Microscopy Methodologies - Gaston, Emily; Woo, Mary; Steele, Clare; Sukumaran, Suja; Anderson, Sean (Applied spectroscopy, 2020)
The abundance and distribution of microplastic (<5 mm) has become a growing concern, particularly over the past decade. Research to date has focused on water, soil, and organism matrices but generally disregarded air. We explored airborne microplastic inside and outside of buildings in coastal California by filtering known volumes of air through glass fiber filters, which were then subsequently characterized with a variety of microscopy techniques: gross traditional microscopy, fluorescent microscopy following staining with Nile red, micro-Raman spectroscopy, and micro-Fourier transform infrared (µFT-IR) spectroscopy. Microplastics permeated the air, with indoor (3.3 ± 2.9 fibers and 12.6 ± 8.0 fragments m ; mean ± 1 SD) harboring twice as much as outdoor air (0.6 ± 0.6 fibers and 5.6 ± 3.2 fragments m ). Microplastic fiber length did not differ significantly between indoor and outdoor air, but indoor microplastic fragments (58.6 ± 55 µm) were half the size of outdoor fragments (104.8 ± 64.9 µm). Micro-Raman and FT-IR painted slightly different pictures of airborne plastic compounds, with micro-Raman suggesting polyvinyl chloride dominates indoor air, followed by polyethylene (PE) and µFT-IR showing polystyrene dominates followed by PE and polyethylene terephthalate. The ubiquity of airborne microplastic points to significant new potential sources of plastic inputs to terrestrial and marine ecosystems and raises significant concerns about inhalation exposure to humans both indoors and outdoors.